DETECTION of MOGIBACTERIUM TIMIDUM IN SUBGINGIVAL BIOFILM of AGGRESSIVE and NONDIABETIC and DIABETIC CHRONIC PERIODONTITIS PATIENTS - Viana Casarin, Renato Correa [UNESP]; Saito, Daniel; Santos, Vanessa Renata; Pimentel, Suzana Peres [UNESP]; Duarte, Poliana Mendes; Casati, Marcio Zaffalon [UNESP]; Goncalves, Reginaldo Bruno (Soc Brasileira Microbiologia, 2012)
The aim of the present study was to evaluate the frequency of detection of Mogibacterium timidum in subgingival samples of subjects with generalized aggressive periodontitis (GAgP) and uncontrolled diabetic and non-diabetic subjects with generalized chronic periodontitis (GChP). 48 patients with GAgP, 50 nondiabetic and 39 uncontrolled (glycated hemoglobin >7%) type 2 diabetic subjects with GChP were enrolled in this study. Subgingival biofilm were collected from deep pockets (probing depth > 7 mm). After DNA extraction, M. timidum was detected by Nested Polymerase Chain Reaction and chi-square test was used to data analysis (p>0.05). There were no differences in the frequency of detection of M. timidum between subjects with GAgP (35%) and non-diabetic subjects with GChP (40%) (p>0.05). The frequency of detection of M. timidum was significantly higher in deep pockets of diabetic subjects with GChP (56%) when compared to GAgP (p<0.05), but similar to non-diabetic subjects with GChP (p>0.05). The frequency of detection of M. timidum was higher in subjects GChP presenting uncontrolled type 2 diabetes mellitus, when compared to GAgP subjects.
Keywords: Mogibacterium timidum; Aggressive periodontitis; Chronic periodontitis; Diabetes mellitus